Co-inoculação e pré-inoculação de sementes em soja - Fipke, Glauber Monçon (2015)
New technologies are intended to assist the farmer in the inoculation process, as is the case of antecipated inoculation (pre-inoculation) provided by using osmoprotectors. In search of higher yields, the kind of inoculation and management with nitrogen fertilizer also need to be clarified. In this study, two experiments were conducted to evaluate the agronomic performance of two inoculation strategies with Bradyrhizobium alone (conventional inoculation) or combined with Azsopirillum brasilense (co-inoculation). The first experiment, we evaluated the pre-inoculation (0, 7 and 10 days before seeding). The second experiment evaluated the response to supply urea (0, 75 and 150 kg N ha-1) split into two periods of three soybeans cultivars development stage (BMX Ativa RR, TEC 6029 IPRO and BMX Potência RR). We evaluated the interaction of nodulation, of morphophysiological components and grain yield at conditions of Santa Maria. Co-inoculation and conventional inoculation, both plus an osmoprotectors, showed increases in grain yield relative to treatment not inoculated 31 and 25%, respectively. With seven days before to sowing, use of osmoprotectors for both types of inoculation, did not differ statistically from the other treatments inoculated the same day of sowing. Co-inoculation provided increment in grain yield of 240 kg ha-1 compared to conventional inoculation. BMX Ativa, TEC 6029 IPRO and BMX Potência when co-inoculated showed increases in grain yield 6, 4 e 12%, respectively. The addition of 150 kg N ha-1 for the two indeterminate cultivars had an increases, but without economic return. The cultivars tested when inoculated conventionally not respond positively to the application of urea. Therefore, these results confirm the effectiveness of the use osmoprotectores and co-inoculation ond the seeds and low economic returns provided by the use of nitrogen fertilizer. It emphasizes the use of activation and protection substances on rhizobial inoculants for the formulation, as well as more studies concerning the efficiency of co-inoculation with rhizobacteria promote plant growth to obtain higher yields.